Dosimetric test of a small laboratory animal phantom created by fused filament fabrication; Инновационные технологии ядерной медицины и лучевой диагностики и терапии - Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Bulavskaya A. A. Angelina Aleksandrovna; Bushmina E. A. Elizaveta Alekseevna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich (2023, 2023)
Текстовый файл